Sexual health and sexually transmitted diseases knowledge: insights from a large-scale university student survey in Ho Chi Minh City, Vietnam - Phan, Van Tien; Huynh, Thuc Quyen; Tran, Doan Hong Ngoc; Le, Nhat Thong; Duong, Doan Minh Trung; Do, Thi Thu Hien; Nguyen, Minh Huyen Trang; Phan, Thi Sam; Nguyen, Cao Nguyen; Le, Thi Van Anh; Dang, Trinh Minh Anh; Le, Minh Thong; et al. (Tạp chí Y Dược Huế, 2025)
Background: Sexually transmitted diseases (STDs) are a critical public health issue affecting millions worldwide, with significant repercussions on sexual and reproductive health. This study aims to evaluate the knowledge, attitudes of STDs of university students in Ho Chi Minh City and to identify key socio-demographic factors influencing their awareness. Method: A cross-sectional survey was conducted using a structured questionnaire, including the participants’ demographic and their knowledge of sexual health (15 items) and STDs (43 items), sexual behavior and attitude toward STD. Differences in STDs knowledge were statistically assessed using Kruskal-Wallis, t-tests and Chi-squared tests. Results: The study garnered 19,251 valid responses from students across various academic disciplines and demographic backgrounds. The insights revealed a moderate level of knowledge about sexual health and STDs among the student population. Factors such as gender, field of study, and urban versus rural upbringing significantly influenced knowledge levels. Students majoring in health-related fields and those from urban areas had better understanding, while those who grew up in rural areas or from non-health disciplines demonstrated lower knowledge level. Some misconceptions regarding STDs transmission and prevention remained prevalent, including the belief that condom can completely prevent STDs transmission. Conclusions: This study underscores gap in knowledge level and discusses the effect of stigma on perception and behavior. The results provide a foundation for developing targeted interventions aimed at improving STDs awareness and preventative practices among university students in Vietnam. Educational institutions need to play a more active role in providing accurate, accessible, and engaging educational program, as well as creating a supportive environment for open discussions about sexual health.